Culture rules the leader's guide to creating the ultimate competitive advantage - Miller, Mark. (Dallas Matt Holt Books, 2023)
Culture Rules makes the case for why leaders should invest their time and energy on building culture and gives them three simple, actionable rules they must play by if they want to stay in the game and win!
Includes bibliographical references and index.
Keywords: Corporate culture